The relationship between people's activities and values with the protection level and biodiversity - Tolvanen, Anne; Kangas, Katja; Tarvainen, Oili; Huhta, Esa; Jäkäläniemi, Anne; Kyttä, Marketta; Nikula, Ari; Nivala, Vesa; Tuulentie, Seija; Tyrväinen, Liisa (Butterworth Scientific Ltd., 2020)
We investigated how people's recreational activities, values, and land use preferences are related to the protection level, biodiversity and cultural heritage values of nature-based tourism areas in northern Finland. We assessed peoples' opinions using a public participation geographic information system (PPGIS) and analyzed the data together with spatial biodiversity and cultural heritage data from the same area. Associations between the PPGIS place markings with the protection level and biodiversity values were quite low, and for the cultural heritage sites they were altogether missing. Negative preferences were often marked in areas with high numbers of sites rated as pleasant and they overlapped with each other, indicating conflicting preferences. Since most activities are not noticeably related to the protection level or biodiversity values of a site they can be planned so as to protect the biodiversity of the area.
Keywords: Conflicts; Factor analysis of mixed data; Land use planning; Nature protection; Public participation GIS; Reconciliation; Tourist resort